Treatment patterns and adverse events of antiseizure medications among adult patients with epilepsy: a single centre observational cross-sectional study in Northern Sri Lanka - Thiyahiny, S.N.; Yalini, G.; Ajantha, K. (Springer, 2026)
Background: Antiseizure medications (ASMs) are essential for seizure control, but they are also associated with a range of adverse events that may affect treatment outcomes. Objective: This study aimed to evaluate the treatment pattern and adverse events of ASMs among adult patients with epilepsy who were followed up at a tertiary-care hospital in Northern Sri Lanka. Methods: A descriptive cross-sectional study was conducted among adult patients on ASMs for ≥ 3 months who were receiving follow-up at Teaching Hospital Jaffna. Data were collected over four months using a pretested interviewer-administered questionnaire. Chi-square test and logistic regression were performed to determine the significance between groups and the association of independent variables, respectively. A p-value of ≤ 0.05 was considered statistically significant. Results: Data from 213 participants was analysed. The mean age was 36.27 ± 0.92 years, and the male-to-female ratio was almost 1. Nearly two-thirds of participants (64.8%) were on dual or polytherapy. Older ASMs were predominantly prescribed (74.5%). A total of 333 adverse events were reported, giving a point prevalence of 68.5% and a rate of 1.6 adverse events per person. Sedation (27%), memory impairment (24%), and dizziness (21%) were the most common adverse events. Advancing age (adjusted OR (AOR): 4.3, 95% CI 1.87 to 10.29, p < 0.001), early onset of epilepsy (AOR: 0.35, 95% CI 0.14 to 0.87, p = 0.023), and the use of multiple ASMs (AOR: 2.7, 95% CI 1.4 to 5.3, p = 0.003) were associated with the occurrence of adverse events. Carbamazepine, clobazam and valproic acid were significantly (p < 0.05) associated with one or more common adverse events. Conclusion: Most patients in this study received older antiseizure medications and polytherapy. A high burden of adverse events linked to antiseizure medications was also observed. Studies with larger samples are needed to determine the safety and efficacy of current practices and to plan treatment strategies to optimise the epilepsy care.
Keywords: Epilepsy; Antiseizure medications; Adverse events; Sri Lanka